Public Awareness and Behavior Change for Climate Conscious Actions - Ursula seventry, Maria; Florent, Fiorenza; Calvin, Calvin (Journal Social Humanity Perspective, 2023)
Global action is urgently needed to address the serious threat that climate change poses and to advance sustainability in the twenty-first century. Raising public awareness and encouraging behaviour change toward eco-friendly methods are essential to the success of this effort. The understanding of human behaviour in relation to climate change is explored in this essay along with the most recent research trends in these fields. Focuses on efficient communication tactics and behavioural changes that can encourage both individual and collective climate-conscious behaviour. To thoroughly explore the elements impacting climate change beliefs and behaviour change drivers, the technique used in this study employs a mixed-methods approach, integrating quantitative surveys and qualitative interviews. Researchers get better insights into the complexity of human decision-making processes and the possible levers for long-lasting behaviour modification by integrating various data sources. The results highlight the significance of efficient communication techniques in closing the knowledge-action gap. Messages about climate change can be tailored, social norms can be used, and visual communication features can be used to increase engagement and favourably affect attitudes. Behavioural interventions have been helpful in encouraging sustainable habits and long-term behaviour change. This document offers a number of evaluation criteria and techniques to evaluate the effectiveness of public awareness campaigns and initiatives. These include tracking adjustments in attitudes and perceptions, examining behavioural changes, gauging media involvement, and assessing knowledge and awareness changes. The study highlights the value of performing thorough evaluations to guide decision-making based on evidence and improve communication tactics for optimum impact.